Chanacomchana: um sopro do lesbianismo paulista nos anos de 1980 - Batista, Letícia Emília (2020)
Starting from the concept of compulsory heterosexuality, in which we are all included, talking about lesbians is to represent a contradiction to the naturalized order of male domination. Based on a historical analysis, this dissertation seeks to understand how the Chanacomchana newsletters contributed as a discursive reference for its visibility and as lesbian experiences in the 1980s. It was initially about rescuing the Galf background and its relations with the homosexual and feminist movement, by having influenced the emancipation of this lesbian group. Subsequently, an epistemological survey was carried out using reports to understand how feminist and lesbian productions affected publications. And finally, it was a question of showing how these sources contributed to violate a model of sexuality, forming a network that breaks loneliness and reveals how these women fought for their spaces and how their narratives built identities and transformed them into subjects with the right to talking and listening